A Pathological Study of Ovarian Abnormalities in Slaughtered NonPregnant Cows in Sulaimani Province. - Mohammed, Mardin O.; Amin, Faraidoon A.S.M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The current study was conducted to address the pathological conditions of ovaries of cows slaughtered at the abattoir in Sulaimani province, Kurdistan Region-Iraq. Among the 404 genitalia samples collected from the non-pregnant animals, 206 (51%) were found without gross pathological abnormalities (with cyclic activity) and the remaining 120(29.70%)samples were found with gross pathological abnormalities of ovaries. The ovaries exhibited the highest percentage of lesions 29.70%. Detected ovarian lesions included follicular cyst 10.89%, cystic corpus luteum 5.44%, mild ovariobursal adhesions 4.45 %, sever ovariobursal adhesion 0.25%, paraovarian cysts 3.22%, ovarian hypoplasia 1.98%, ovarian hemorrhage (hemorrhagic cystic corpus luteum) 1.48%, luteal cyst 1.24%, ovarian agenesis 0.50% and ovarian tumor (Gonadoblastoma) 0.25%. Histopathological examinations exhibited that the follicular cysts were lined by several layers of granulosa and theca cell, while the luteal cysts had follicular granulsa and the theca cells with marked luteinization of cytoplasm. Microscopically, the ovarian hypoplasia showed lack of ovarian follicles and oocytes, while the cavities of paraovarian cysts were lined by a single layer of cuboidal epithelial cells, and the hemorrhagic cyst showed scattered hemorrhagic spots close to the lumen and luteinized of granulosa and theca cells layers of cystic wall. Histopathologically, the ovarian gonadoblastoma (Dysgenentic gonadoma) was characterized by dual population of germ cell tumor and sex-cord stromal tumor and this observation has not been recorded in Iraq previously. It was concluded that ovarian abnormalities constitutes an percentage 0f 29.70%. And ovarian gonadoblastoma was firstly recorded in this study in Iraq.
Keywords: ovaries; abnormalities,nonpregnant cows,follicular cyst; ovariangonadoblastoma